HOXA1 Is an Antagonist of ERα in Breast Cancer - Belpaire, Magali; Ewbank, Bruno; Taminiau, Arnaud; Bridoux, Laure; Deneyer, Noémie; Marchese, Damien; Lima-Mendez, Gipsi; Baurain, Jean-François; Geerts, Dirk; Rezsohazy, René (Frontiers in Oncology, 2021)
Breast cancer is a heterogeneous disease and the leading cause of female cancer mortality worldwide. About 70% of breast cancers express ERα. HOX proteins are master regulators of embryo development which have emerged as being important players in oncogenesis. HOXA1 is one of them. Here, we present bioinformatic analyses of genome-wide mRNA expression profiles available in large public datasets of human breast cancer samples. We reveal an extremely strong opposite correlation between HOXA1 versus ER expression and that of 2486 genes, thereby supporting a functional antagonism between HOXA1 and ERα. We also demonstrate in vitro that HOXA1 can inhibit ERα activity. This inhibition is at least bimodal, requiring an intact HOXA1 DNA-binding homeodomain and involving the DNA-binding independent capacity of HOXA1 to activate NF-κB. We provide evidence that the HOXA1-PBX interaction known to be critical for the transcriptional activity of HOXA1 is not involved in the ERα inhibition. Finally, we reveal that HOXA1 and ERα can physically interact but that this interaction is not essential for the HOXA1-mediated inhibition of ERα. Like other HOX oncoproteins interacting with ERα, HOXA1 could be involved in endocrine therapy resistance.